Controlling Chemical Waves by Transforming Transient Mass Transfer. Issue 3 (18th November 2021) - Zhang, Zeren; Xu, Liujun; Huang, Jiping
Abstract: Manipulating transient mass transfer plays a crucial role in physics, chemistry, biology, and other fields. One typical example is chemical waves, whose concentration profiles have spatiotemporal variations. Based on a general model associated with the advection‐diffusion equation, an optimized transformation‐mass‐transfer theory is proposed to flexibly control transient mass transfer. As an example application, a class of separators is theoretically designed to achieve the separation of chemical waves. Meanwhile, three typical types of devices for cloaking, concentrating, and rotating chemical waves are proposed successfully, thus offering more versatile control methods. Such theoretical analysis is well confirmed by the computer simulations. These results provide insights into novel manipulation of chemical waves associated with biochemical reactions and promote potential applications for transient mass diffusion. Abstract : Transient mass transfers like chemical waves can be manipulated according to the optimized‐transformation transient‐mass‐transfer theory. A cloak, concentrator, rotator, and separator are designed for chemical waves. The results provide different insights into advanced manipulation of chemical waves associated with biochemical reactions and promote potential applications for transient mass diffusion.